2021
DOI: 10.5114/ceji.2021.109195
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol alleviates sepsis-induced acute kidney injury by deactivating the lncRNA MALAT1/MiR-205 axis

Abstract: Introduction:Resveratrol plays a protective role against sepsis development, and the long noncoding Rna (lncRna) maLaT1 is an inflammation-relevant biomarker. This investigation attempted to reveal whether resveratrol attenuated inflammation of sepsis-induced acute kidney injury (aKi) by regulating maLaT1.Material and methods: in total 120 rats were divided into a control group (n = 20), a Sham group (n = 20), a sepsis group (n = 40) and a resveratrol group (n = 40), and serum levels of inflammatory cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Resveratrol seems to modulate several miRNAs involved in inflammatory pathways, such as the proinflammatory miR-155, the anti-inflammatory miR-663, and the oncogenic miR-21 21 ( Latruffe et al, 2015 ). A recent study has also reported the potential involvement of the lncRNA MALAT-1, a biomarker of inflammation ( Wang et al, 2021 ). Treatment with resveratrol in rats with sepsis-induced kidney damage was associated with lower circulating concentrations of this lncRNA compared to untreated animals ( Wang et al, 2021 ).…”
Section: Inflammatory Statesmentioning
confidence: 99%
See 4 more Smart Citations
“…Resveratrol seems to modulate several miRNAs involved in inflammatory pathways, such as the proinflammatory miR-155, the anti-inflammatory miR-663, and the oncogenic miR-21 21 ( Latruffe et al, 2015 ). A recent study has also reported the potential involvement of the lncRNA MALAT-1, a biomarker of inflammation ( Wang et al, 2021 ). Treatment with resveratrol in rats with sepsis-induced kidney damage was associated with lower circulating concentrations of this lncRNA compared to untreated animals ( Wang et al, 2021 ).…”
Section: Inflammatory Statesmentioning
confidence: 99%
“…A recent study has also reported the potential involvement of the lncRNA MALAT-1, a biomarker of inflammation ( Wang et al, 2021 ). Treatment with resveratrol in rats with sepsis-induced kidney damage was associated with lower circulating concentrations of this lncRNA compared to untreated animals ( Wang et al, 2021 ). Moreover, resveratrol reduced the intracellular concentrations of key pro-inflammatory cytokines, i.e., TNF-α, IL-1β and IL-6 ( Wang et al, 2021 ).…”
Section: Inflammatory Statesmentioning
confidence: 99%
See 3 more Smart Citations